Pengaruh Pemahaman Konsep Matematis Siswa Pada Kurikulum Merdeka Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 3 Baubau - Armin, Rismayani; Minarni, Minarni (Jurnal Akademik Pendidikan Matematika, 2024)
The aim of this research is to determine the effect of students’ understanding of mathematical concepts in the Merdeka Curriculum on the learning outcomes of class VIII students at SMP Negeri 3 Baubau. This research is an ex post facto research methods. The population in this study were all students in class VIII, even semester, SMP Negeri 3 Baubau, consisting of 195 students. The sample in this study consisted of classes VIII B and VIII C with a total of 58 students. The instruments used in this research were diagnostic test questions in the form of essays, questionnaires and documentation. This research data collection technique was obtained by observation, documentation, tests and questionnaires. Data analysis techniques use descriptive analysis and inferential analysis. The results of the research show that students’ understanding of mathematical concepts in the Merdeka curriculum when completing diagnostic test questions on student learning outcomes, in this case the report card scores obtained in the odd semester, based on the results of calculations using simple linear regression, obtained a sig value of 0.00 for a significance level value of 0.05 (5%). Thus, the significant value is 0.00 < 0.05, so H1 is accepted. So it can be concluded that there is an influence of students’ understanding of mathematical concepts in the Merdeka curriculum on the learning outcomes of class VIII students at SMP Negeri 3 Baubau.